A new species of Aculops (Acari: Prostigmata: Eriophyidae) from Serbia on Dipsacus laciniatus L. (Dipsacaceae), a weed target of classical biological control in the United States of America - Rector, Brian; Petanović, Radmila U. (Zootaxa, 2012)
A new eriophyoid mite species, Aculops orlovacae n. sp. (Acari: Prostigmata: Eriophyidae) collected from Dipsacus laciniatus L. (Dipsacaceae) in northern Serbia, is described and illustrated, including digital micrographs depicting key morphological characters. Differential diagnosis is provided in comparison with Aculops salixis Xue, Song et Hong, Aculops rhodensis (Keifer), Aculops hussongi Keifer and Aculops oblongus (Nalepa). This is the first eriophyoid mite species in the genus Aculops described from a host plant in the family Dipsacaceae and it is only the second eriophyoid known from a host species in the genus Dipsacus L. This mite was found during surveys for natural enemies of Dipsacus spp., as part of a classical biological control program.